A New Approach to The Treatment of Chronic Generalized Catarrhal Gingivitis - Oxunjonova Xayotxon Xosiljonovna (Scientific Trends, 2023)
This paper presents the results of treatment and prevention of chronic catarrhal gingivitis by including a rinse aid based on plant components in a complex of individual hygienic measures, which determines its antiseptic and anti-inflammatory effect. Also included in the rinse aid is fluoride, which has an anti-carious effect, which makes it possible to recommend it for the daily prevention of periodontal diseases and caries. The study involved 40 patients aged 18-28 years with a diagnosis of chronic generalized catarrhal gingivitis, who were divided into two groups. The comparison group (20 people) received treatment according to the generally accepted standard scheme, the main group (20 people) received standard therapy and a rinse aid. The analysis of the obtained results showed the clinical effectiveness of the use of the rinse aid in a complex of individual hygiene measures, having a positive effect on reducing the time of relief of the inflammatory process in periodontal. Daily use of a rinse aid based on plant components and fluoride inhibits the reproduction of pathogenic microflora of dental plaque and creates conditions for prolonged remission of catarrhal gingivitis.
Keywords: periodontal diseases, chronic catarrhal gingivitis, oral hygiene.